Processes and progresses of the Ethiopian harmonized DST - Moltote, Feben Assefa; Cherenet, Meklit; Abera, Wuletawu; Desta, Gizaw; Desta, Lulseged; Tilaye, Amsalu; Rozarios, GIlbert; Desalegn, Henok; Mukund, Patil; Degefie, Tibebe; Kinde, Tesfaye; Sida, Tesfaye; et al. (2025)
Ethiopia’s efforts to increase agricultural productivity have increasingly focused on efficient, site-specific fertilizer use. In recent years, national and international partners, supported by major donors, developed advanced fertilizer advisory approaches for key staple crops. While scientifically robust, these efforts resulted in fragmented tools and datasets, limiting national scalability. In response, the Ministry of Agriculture convened government agencies, research institutions, CGIAR centers, and donors in 2023 to align these initiatives into a harmonized national system. This collaboration, led by the Ethiopian Institute of Agricultural Research with CGIAR modeling support and contributions from CIAT–Bioversity, CIMMYT, ICRISAT, regional research centers, and GIZ, was catalyzed by donor support—particularly from BMGF, USAID, and GIZ. Between 2024 and 2025, partners jointly developed and validated a harmonized fertilizer Decision Support Tool (DST) for maize, wheat, tef, and sorghum. The DST integrates multi-year national field trial data with soil and climate information to generate site-specific fertilizer recommendations that reflect local biophysical conditions and seasonal climate risk. Designed as a living platform, the system can continuously incorporate new data and improve advisory quality over time. Extensive on-farm validation confirmed the robustness and adaptability of DST across diverse agroecological zones. In parallel, targeted capacity building strengthened Ethiopia’s National Agricultural Research System to independently operate, update, and sustain the tool. By 2025, DST had transitioned from a research initiative into a nationally owned platform embedded within government-led validation programs and multiple farmer-facing delivery pathways. The harmonized DST is now being scaled through partnerships with extension services, digital advisory platforms, and private-sector service providers, linking agronomic recommendations with input access, credit, and risk management. Overall, the experience demonstrates how coordinated donor investments, strong government leadership, and CGIAR science can be integrated into a scalable and sustainable national system that addresses key sustainable farming challenges in Ethiopia, while driving productivity growth, climate resilience, and more efficient use of inputs among smallholder farmers.